2008
DOI: 10.1161/hypertensionaha.107.105387
|View full text |Cite
|
Sign up to set email alerts
|

Renal Phosphodiesterase 4B Is Activated in the Dahl Salt-Sensitive Rat

Abstract: Abstract-Reduced ␤-adrenoreceptor signaling is associated with increased sympathoadrenal activity in hypertensive patients and animal models of hypertension. However, the mechanism that accounts for this characteristic decline in ␤-adrenergic signaling is unclear. In the present study, we investigated renal phosphodiesterase 4B, which metabolizes cAMP. Immunoblot analysis detected only the phosphodiesterase 4B4 isoform present in kidney tissue from spontaneously hypertensive rats, hypertensive Dahl salt-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previous studies by Tawar et al21 report that the primary renal isoform of PDE4 is PDE4B4. It is conceivable that selective inhibition of PDE4B4 would minimize adverse effects while improving renal hemodynamics and blood pressure in genetic hypertension.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies by Tawar et al21 report that the primary renal isoform of PDE4 is PDE4B4. It is conceivable that selective inhibition of PDE4B4 would minimize adverse effects while improving renal hemodynamics and blood pressure in genetic hypertension.…”
Section: Discussionmentioning
confidence: 96%
“…However, another interpretation is that these effects are observable in 5 weeks-of-age SHR because even very mild elevations in MABP may markedly alter the role of PDE4 in the renal vasculature. Because Tawar et al21 report that the primary renal isoform of PDE4 is PDE4B4, it would be interesting to determine whether this is the isoform of PDE4 responsible for masking the ability of isoproterenol to induced 3′,5′-cAMP in the renal vasculature of SHR.…”
Section: Discussionmentioning
confidence: 99%
“…However, RO 20–1724 does not distinguish among the multiple PDE4 isoforms; indeed, presently no PDE4 inhibitors are available that block exclusively a specific PDE4 isoform. In this regard, there are 4 different PDE4 subtypes (PDE4A, PDE4B, PDE4C and PDE4D) with each subtype being encoded by a specific gene18 and being populated by a set of variants due to alternative mRNA splicing and alternative promoters16, 18. Our real time PCR results demonstrate that the dominant PDE4 mRNA subtype in both PGVSMCs and PGVECs is PDE4B.…”
Section: Discussionmentioning
confidence: 73%
“…At present, studies have identified 5 different variants of PDE4B16. Real time PCR was conducted using primers designed to recognize the 5 specific variants of PDE4B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation